Efektivitas Metode Biblioterapi terhadap Pengetahuan Remaja Putri tentang Menarche di Sekolah Dasar - Widya Mayang Anggraeni; Dini Kurniawati (Griya Widya: Journal of Sexual and Reproductive Health, 2022)
Background: Menarche is the first menstruation experienced by women. Knowledge of physical and psychological changes related to menarche is needed by young women, especially those who have not experienced menstruation to prepare themselves to face menarche. The bibliotherapy method can provide effective benefits because the reading material in bibliotherapy has specific story content, according to the characteristics of the subject and contains learning values ​​so that it can be used as a method that has the power to change. Method: The design of this study was Pre-Experimental with a research design of One Group Pre-test-Post-test Design which used 38 respondents. Sampling used a non-probability sampling technique with a total sampling approach. Collecting data using a questionnaire that was analyzed using the Wilcoxon Signed Rank Test. Result: The results showed that there was an increase in the average knowledge about menarche before and after that was 4.35. The results of the Wilcoxon Signed Rank Test statistical test showed that the value of p = 0.000 <0.05, it can be concluded that "Ha is accepted" which means that there is a significant difference in the knowledge of young women before and after giving the bibliotherapy method. Conclusion: So that the bibliotherapy method is effective to increase the knowledge of young women about menarche at SDN 1 Purwoharjo and can be used as a method to convey information to elementary students